2013
DOI: 10.3389/fnhum.2013.00426
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory characteristics of the visual mismatch negativity: what evoked potentials aren't telling us

Abstract: The visual mismatch negativity (vMMN) response is typically examined by subtracting the average response to a deviant stimulus from the response to the standard. This approach, however, can omit a critical element of the neural response, i.e., the non-phase-locked (“induced”) oscillatory activity. Recent investigations of the oscillatory characteristics of the auditory mismatch negativity (aMMN) identified a crucial role for theta phase locking and power. Oscillatory characteristics of the vMMN from 39 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 46 publications
10
36
2
Order By: Relevance
“…However, in contrast to Stothart and Kazanina, we also found a stronger increase of alpha oscillations (ERS) to deviant than standard stimuli. In our study, the activation of ERD/ERS showed a broad spatial distribution; however, the responses rather had topographies with a clear maximum over occipito-parietal regions, which is in line with ERP vMMN studies (Kimura, 2012) and the study of Stothart and Kazanina (2013).…”
Section: Mismatch Detection In Neuronal Oscillationssupporting
confidence: 89%
See 2 more Smart Citations
“…However, in contrast to Stothart and Kazanina, we also found a stronger increase of alpha oscillations (ERS) to deviant than standard stimuli. In our study, the activation of ERD/ERS showed a broad spatial distribution; however, the responses rather had topographies with a clear maximum over occipito-parietal regions, which is in line with ERP vMMN studies (Kimura, 2012) and the study of Stothart and Kazanina (2013).…”
Section: Mismatch Detection In Neuronal Oscillationssupporting
confidence: 89%
“…Similarly, it has recently been investigated whether induced theta activity plays a similar role in the generation of oscillatory visual MMN as it does in oscillatory auditory MMN (Stothart and Kazanina, 2013). The results by Stothart and Kazanina (2013) showed the reduction of alpha power to both standard and deviant stimuli in occipito-parietal sites. Importantly, the decrease of alpha power was stronger to deviant stimuli like in our study.…”
Section: Mismatch Detection In Neuronal Oscillationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Stothart and Kazanina (2013) investigated differences in phase-locking and induced activity in ERPs to rare unattended changes in spatial frequency of vertical bar stimuli in an oddball paradigm. Participants engaged in a central primary task.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…Oscillatory phase reset may be a fundamental mechanism of potentiation of sensory responses. Indeed, synchronization of the phase of a fluctuating visual stimulus with ongoing oscillatory activity is known to increase the LFP amplitude (Kissinger et al, 2018), and the well-documented increase sensory response amplitudes following directed attention or in response to a deviant stimulus are coincident with an oscillatory phase reset (Fuentemilla et al, 2008;Heinze et al, 1994;Hillyard and Anllo-Vento, 1998;Stothart and Kazanina, 2013;Zhang and Luck, 2009).…”
Section: Discussionmentioning
confidence: 99%